Effect of soybean hulls on blood biochemical profiles and body condition of dogs - Mariana Scheraiber; Tabyta Tamara Sabchuk; Juliana Regina da Silva; Lidiane Priscila Domingues; Tatiane Aparecida Ramos; Ananda Portella Félix; Simone Gisele de Oliveira; Ana Vitória Fischer da Silva (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this study was to evaluate the alterations in blood biochemical profiles and body condition of dogs after intake of the diet without soybean hull (0%SH) and with soybean hull (16%SH) replacing corn. Twelve Beagle dogs with ideal body condition score (BCS) (average: 5) were distributed in a completely randomized design (six animals per treatment) and received the daily amount of food according to the energy needs for maintenance (g/kg weight0.75). The animals were evaluated on days 0 and 28 in relation to the blood biochemical profiles and body measurements, such as: total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low density lipoprotein (VLDL), triglyceride (TAG), glucose, body weight (BW), body fat percentage (%BF), nape, rib, tail base (TB), chest, and abdomen with plicometer, and BCS (scale of 1, thin and 9, obese), canine body mass index (CBMI), and thickness of the adipose tissue of the seventh lumbar vertebra (L7) with ultrasonography. The data were analyzed by Student's t test. The variation (final - initial, mg/dL) of cholesterol (16.33 vs. 15.55), HDL (17.56 vs. 10.05), LDL (22.78 vs. 14.57), VLDL (-4.01 vs. -1.92), TAG (-20.11 vs. -11.66), and glucose (-16.77 vs. -20.31) of dogs fed 0%SH and 16%SH, respectively, showed no difference. The body measurement variation (cm) of TB (1.00 vs. -0.60) obtained a significant difference. The addition of soybean hull in the diet does not alter the blood biochemical profiles; however, it does decrease the deposition of lipids in subcutaneous tissue.